SURVIVAL STRATEGIES FOR TRADITIONAL MARKET TRADERS IN THE DIGITAL ERA - Anggraini Safinka; Khairani; Putri Safa Aulia Lubis; Raisa Aulia Rahmah; Tria Manda Sari (PERSPEKTIF: Journal of Social and Library Science, 2024)
Traditional Markets are facing great challenges from the development of digital technology. This research aims to explore the survival strategies of traditional market traders in the Pajak USU Medan in facing changes in the digital era. The method used is qualitative descriptive with a field approach based on data analysis obtained from interviews and observations. It was found that the results of the study showed that developments in this digital era have a considerable impact on traders in the Pajak USU as for the impact, namely a decrease in the level of buyers, as for the survival strategies carried out by traders, namely by following market trends, maintaining the quality of goods sold, trying to offer their products through social media, and providing the best service to visitors